The mad dog and the Englishman : a critical history of the running amok as sponteneous naked savage : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Art in Psychology at Massey University - Panikkar, Rajeendernath (Massey University, 2005)
I began this work with the intention of writing a genealogy of amok, the Malay malaise, not long now incorporated into the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM), as a culture-bound syndrome. A reading of Foucault's genealogy, and especially of its innumerable critiques, convinced me of the incompatibility of matching an approach steeped in the Western tradition with a 'syndrome' of a people who were long colonised by this West. Foucault's conceptualization, and attributions, of power were also instrumental in my rejection of his incitement to 'write genealogies' (Sawicki, 1991; p. 15), as a method of resisting the 'often oppressive rationalities of discourse in the human sciences' (Lash, 1991; p. 259). In departing from the genealogical approach I have also gravitated to a postcolonial critique of the writing of the Malay and his amok, which I consider to be far more compatible, given his/ her colonisation by a succession of European imperial powers. Not coincidentally, as he is one of Foucault's most vehement critics, I have refracted this critical history of amok through Edward Said's secular-ethical working of the postcolonial thesis. This is my attempt to avoid what Said views to be the 'retreat of intellectual work' from the 'actual society in which it works' (Ashcroft, 2003; p. 264), and into 'the 'labyrinth of textuality' constructed out of 'the mystical and disinfected matter of literary theory' where a 'precious jargon has advanced' (Said, 1983; p. 4). I have then very deliberately attempted to minimise this 'precious jargon' to make this work more accessible. I have not included a literature review in this work and instead furnish the excuse that it is (this work) a literature review of sorts. It is a literary critique of the historical writing of the Malay and his malaise. A final word concerns the likely controversial use of the term, the 'White Man', which reprises a longstanding, and antagonistic, racial dichotomy which I and many others believe to be fundamental to 'modern' history. Though I explain my use of this term in my work, I make my sincere apologies to those who feel aggrieved with my continual reference to the 'White Man'. At times I have felt as aggrieved but, in considering various alternatives, could not in all honesty disregard the only too apparent authority this self-proclaimed 'White Man' has exerted on history, and more particularly, in the context of this thesis, on the Malay World.
Keywords: Malays (Asian people); Psychology; Ethnopsychology; Malaysia